2005
DOI: 10.1007/s11663-005-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Rate of reduction of ore-carbon composites: Part I. Determination of intrinsic rate constants

Abstract: A process for ironmaking was proposed consisting of the combination of a rotary hearth furnace and a bath smelter employing wood charcoal as reductant and energy source. This article examines reactions in composites of iron oxides and carbon at elevated temperatures in conditions developed to minimize the influence of mass and heat transfer to the overall rates. A combined reaction model considering the steps of carbon oxidation and reduction of the iron oxides was developed allowing the measurement of rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…It varies from 228 to 272 kJ/mol and is within the large range of values reported in literature 11,12,14,17,19,31,35,40) as characteristic for the Boudouard reaction.…”
Section: Gasification Rate Of Carbonaceous Reductantssupporting
confidence: 82%
See 3 more Smart Citations
“…It varies from 228 to 272 kJ/mol and is within the large range of values reported in literature 11,12,14,17,19,31,35,40) as characteristic for the Boudouard reaction.…”
Section: Gasification Rate Of Carbonaceous Reductantssupporting
confidence: 82%
“…It ranges from 370 to 280 kJ/mol and corresponds well to the values reported as characteristic for carbon gasification by CO2 under a purely chemical control. 14,17,31,35,40) These values are even slightly higher than those obtained from the gasification tests with pure carbon dioxide (Fig. 5).…”
Section: Limiting Reaction Stepmentioning
confidence: 58%
See 2 more Smart Citations
“…Fortini and Fruehan [16] and Halder and Fruehan [17] reported on the reduction of composite pellets made with charcoal. They showed that the reduction rate of composite pellets made with charcoal is higher than that of comparable pellets made using coal.…”
Section: Introductionmentioning
confidence: 99%